Cryptic diversity of stygobiotic shrimp genus Xiphocaridinella Sadowsky, 1930 (Crustacea: Decapoda: Atyidae): the first case of species co-occurrence in the same cave system in the Western Caucasus - Marin, Ivan (Zootaxa, 2018)
DNA barcoding of stygobiotic shrimps of the genus Xiphocaridinella Sadowsky, 1930 (Crustacea: Decapoda: Atyidae) collected in underground streams flowing inside two neighboring large karst caves (Otap and Abrskil сaves) revealed the presence of two distinct genetic lineages representing the first case of species co-occurrence in the Western Caucasus. The paper presents the complete morphological re-description of stygobiotic atyid shrimp Xiphocaridinella ablaskiri (Birštein, 1939) and the description of a new species using genetic and morphological analysis. Other known cases of co-occurrence of several stygobiotic shrimp species in the same cave system as well as new genetic data (COI mtDNA) on Western Caucasian species of the genus Xiphocaridinella are discussed in the paper.